Prenatal auditory stimulation and impacts on physiological response to feed restriction in broiler chickens at market age - Ahmad-Hanafi, S.; Zulkifli, I.; Ramiah, S.K.; Chung, E.L.T.; Kamil, R.; Sazili, A.Q.; J., Mashitah (Elsevier, 2024)
Feed restriction could induce physiological stress in broiler chickens, leading to welfare issues. Prenatal stimulation could improve stress-coping mechanisms in poultry. The present study aimed to elucidate the effects of subjecting developing embryos to auditory stimulation on physiological stress response to feed restriction in broiler chickens at market age. A total of 423 hatching eggs of Cobb 500 (Gallus domesticus) were subjected to the following auditory treatments: 1) no additional sound treatment other than the background sound of the incubator's compressors at 40 dB (CONTROL), 2) exposure to pre-recorded traffic noise at 90 dB (NOISE), and 3) exposure to Mozart's Sonata for Two Pianos in D Major, K 488 at 90 dB) (MUSIC). The NOISE and MUSIC treatments were for 20 min/h for 24 h (a total of 8 h/d), starting from embryonic days (ED) 12 to hatching. On d 42, an equal number of birds from each prenatal auditory stimulation (PAS) group were subjected to either ad libitum feeding (AL) or 30-h of feed restriction (FR) in a completely randomised design. The FR chickens exhibited significantly higher serum levels of corticosterone (CORT), and heat shock protein (HSP) 70 compared to those of AL. Prenatal auditory stimulation, particularly NOISE, led to lower serum levels of CORT and alpha-1-acid glycoprotein (AGP) levels compared to the CONTROL group. Additionally, NOISE significantly increased brain mRNA glucocorticoid receptor and HSP70 gene expression. The cecal population of E. coli and Lactobacillus spp. was not significantly affected by prenatal auditory stimulation. In conclusion, our findings suggest that prenatal auditory stimulation, particularly NOISE, positively impacts broiler chickens' ability to cope with feed restriction. © 2024